Manifestation of parental support for primary form students learning at home - Monika Zilinskyte; Kazlauskiene, Ausra (Technium Social Sciences Journal, 2020)
The research deals with the parental support for primary form student learning at home. The following problem questions were raised: what are the types of parental involvement in children’s learning and how does parental support manifest in practice of children learning at home. The problem is also relevant because the primary form students’ age is the time when parent support has the highest value and creates conditions for comprehensive personality growth: academic skills, children’s future prospects, mental health and formation of social relationships. By applying the data collection method of in-depth interview, the conditions to understand what types of parental involvement in children’s learning manifest while providing learning support at home have been created. The method of content analysis helped to reveal the following types of parental involvement in children’s learning: control and autonomy supportive practice. Expression of the said roles manifested during the following parents’ initiatives/ actions: collaboration, motivation, intrusion of rules, instructions of parents, preaching, continuous observation.